Oral and dental health in head and neck cancer survivors. Issue 1 (December 2016) - Samim, Firoozeh; Epstein, Joel; Zumsteg, Zachary; Ho, Allen; Barasch, Andrei
Abstract Therapeutic improvements and epidemiologic changes in head and neck cancer (HNC) over the last three decades have led to increased numbers of survivors, resulting in greater need for continuing management of oral and dental health in this population. Generally, the HNC patient oral health needs are complex, requiring multidisciplinary collaboration among oncologists and dental professionals with special knowledge and training in the field of oral oncology. In this review, we focus on the impact of cancer treatment on oral health, and the oral care protocols recommended prior to, during and after cancer therapy. The management of oral complications such as mucositis, pain, infection, salivary function, taste and dental needs are briefly reviewed. Other complications and their management, including osteonecrosis of the jaw and recurrent/new primary malignancies are also described. This review offers clinical protocols and information for medical providers to assist in understanding oral complications and their management in HNC patients and survivors, and their oral and dental health care needs. Oral and dental care is impacted by the patient's initial oral and dental status, as well as the specific cancer location, type, and its treatment; thus, close communication between the dental professional and the oncology team is required for appropriate therapy.